SATB1 as oncogenic driver and potential therapeutic target in head & neck squamous cell carcinoma (HNSCC) - Panchal O; Wichmann G; Grenman R; Eckhardt L; Kunz-Schughart LA; Franke H; Dietz A; Aigner A (United Kingdom, 2025)
The Special AT-rich sequence binding protein 1 (SATB1) is a genome organizer protein that controls gene expression of numerous genes by regulating chromatin architecture and targeting chromatin-remodeling/-modifying enzymes onto specific chromatin regions. SATB1 is overexpressed in various tumors. In head and neck squamous cell carcinoma (HNSCC), SATB1 upregulation is correlated with TNM classification, metastasis, poor prognosis and reduced overall survival. In this paper, we comprehensively analyze cellular and molecular effects of SATB1 in a large set of primary cell lines from primary HNSCC or metastases, using RNAi-mediated knockdown in vitro and, therapeutically, in tumor xenograft mouse models in vivo. In a series of 15 cell lines, major differences in SATB1 levels are observed. In various 2-D and 3-D assays, growth inhibition upon efficient siRNA-mediated SATB1 knockdown depends on the cell line rather than initial SATB1 levels. Inhibitory effects are found to be based on cell cycle deceleration, apoptosis induction, decreased HER3 and Heregulin A&B expression, and effects on EMT genes. In vivo, systemic treatment of tumor xenograft-bearing mice with siRNAs formulated in polymeric nanoparticles inhibits tumor growth of two HNSCC xenograft models, resulting from therapeutic SATB1 reduction and concomitant decrease of proliferation and induction of apoptosis. In conclusion, SATB1 represents a promising target in HNSCC, affecting crucial cellular processes and molecular pathways.